Pengaruh Literasi Keuangan, dan Kepribadian Terhadap Perilaku Manajemen Keuangan - Mohammad Arridho Nur Amin (ICON Publisher, 2024)
The purpose of this study was to determine whether Financial Literacy and Personality affect Financial Management Behavior in MSME actors in Suradadi District, Tegal Regency. The population in this study were MSME actors in Tegal Regency in Suradadi District with a total of 137 respondents, while the sample in this study was 102 MSME actors. The sample collection techniques used were observation, interview, questionnaire, and documentation methods. The analysis used in this study includes validity testing, reliability testing, classical assumption testing, and hypothesis testing. The analysis technique used is multiple linear analysis. The results of the study stated that there was an influence of financial literacy on financial management behavior, personality had a positive effect on financial management behavior, and financial literacy, and personality had a positive effect simultaneously on financial management behavior in culinary MSME actors in Suradadi District, Tegal Regency.